Duel to the Death? The Emblematic Decoration of Fifteenth Century Pole Hammers. (3rd July 2022) - Marek, Lech
Abstract : This study presents the interpretation and contextualisation of apotropaic imagery and inscriptions found on two fifteenth century hammers for use on foot. One of them resides at the Metropolitan Museum of Art, New York (Acc. No. 14.25.1336). The other, its counterpart known only from archival sources, is missing from the collection of the Badisches Landesmuseum in Karlsruhe (Acc. No. G43). The nearly identical form of both hammers and the character of the decoration engraved on their shafts suggests they were produced in the same workshop, perhaps even created by the same hand. Evidence described below supports the argument that the weapons may have been designed for judicial combat.